(3GdQTGO aj TQM GdEQTGOs - (3fhQGdOjf eMeO Hf Ydj Hf eMeO Hf Ydj GdTQja GdMSjfj GdLQLGfj (B((3GHf GdTQja GdLQLGfj(B)s; (3GdSYO GdJaJGRGfj , SYO GdOjf eSYhO Hf YeQ Hf YHO Gddg GdJaJGRGfj,J (B793 (3g` s
(3ChdgG (B:s
(3CeG HYO, ajbhd Ef eNJUQ GdEQTGO GdgGOj fMh GdQTGO GdefShH Edi SjHhjg GdKGfj s
(3BNQgG (B:s
(3Ch GSJagGekG fMh(B: (3gd JPgHjf Ch YQVkG fMh(B: (3CdG JfRdjf Cf JefjkG fMh(B: (3djJc JNQLfj hdjcf gVG BNQ eG C(B{(3OfG EjQGOg aj TQM eNJUQ GdQTGO s
(3hCKQ WeSs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3TQM hGNJUGQs
Keywords: (3GdfMhs